Tool wear and surface roughness on milling carbon fibre reinforced plastic using chilled air - Muhamad Khairussaleh, Nor Khairusshima; Che Haron, Che Hassan; A. Ghani, Jaharah; A.K.M., Nurul Amin (Asian Economic and Social Society, 2012)

(untitled)
Carbon fiber-reinforced plastic (CFRP) composite is an expensive material that is widely used in aerospace applications because of its unique properties. During machining, several problems arise because of the carbon in CFRP. Abrasive wear occurs on the cutting tools during CFRP machining, thereby shortening the life of the tools and damaging surface quality. In this study, the performance of the solid carbide end tool and the surface quality of CFRP composite during the milling process were investigated. A cutting speed ranging from 160 m/min to 200 m/min and a feed rate ranging from 0.025 mm/rev to 0.05 mm/rev were used in the experiment. Results show that tool wear is higher at higher feed rates and lower cutting speeds, whereas longer tool life is achieved at lower feed rates and intermediate cutting speeds. Furthermore, a good machined surface is produced at higher cutting speeds and higher feed rates.